(3ebGdI (B( (3aj GdcdGe (B) (3aj Cf GdCaYGd Ndb Gddg hGcJSGH ddYHGOs - (3GHf YOj , jMji Hf YOj Hf MejO Hf RcQjG, CHh RcQjG,J (B364 (3g` s
(3ChdgG (B:s
(3dhdG JhNi ef ehGabJc GOGe Gddg Jhajbc bGd GdeMJL dG jNdh CaYGd GdaGVdjf ef GMOi KdK LgGJ GeG Gf jchf NdbkG ddg YR hLd s
(3BNQgG (B:s
(3hgPG GjVkG eMGd dCfg jhLH Gf jchf gPG GdGcJSGH hgh MGOK dG eMOK dg hGddg hdi JhajbfG s
(3Vef eLehY , JQJjHgG (B: (3GdKGef YTQs
(3GfXQg eY GdeNWhW Qbe (B302 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3cJH HgG jMji Hf YOi Edi CHj YeQh SYO Hf GdRjOi Hf SYjO ai fbV GdMLL GdJi GfbOgG Gdjg ai fUQI bhd GdbGFdjf Cf GdGaYGd Ndb Gddg hGcJSGH ddYHGOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B156 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B211s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds